Assessment of ischaemic burden in angiographic three-vessel coronary artery disease with high-resolution myocardial perfusion cardiovascular magnetic resonance imaging. (3rd February 2014) - Motwani, Manish; Maredia, Neil; Fairbairn, Timothy A.; Kozerke, Sebastian; Greenwood, John P.; Plein, Sven
Abstract: Aims: This study compared the myocardial ischaemic burden (MIB) in patients with angiographic three-vessel coronary artery disease (3VD) using high-resolution and standard-resolution myocardial perfusion cardiovascular magnetic resonance (perfusion CMR) imaging. Methods and results: One hundred and five patients undergoing coronary angiography had two separate stress/rest perfusion CMR studies, one with standard-resolution (2.5 mm in-plane) and another with high-resolution (1.6 mm in-plane). Quantitative coronary angiography was used to define patients with angiographic 3VD. Perfusion CMR images were anonymized, randomly ordered and visually reported by two observers acting in consensus and blinded to all clinical and angiographic data. Perfusion was graded in each segment on a four-point scale and summed to produce a perfusion score and estimate of MIB for each patient. In patients with angiographic 3VD ( n = 35), high-resolution acquisition identified more abnormal segments (7.2 ± 3.8 vs. 5.3 ± 4.0; P = 0.004) and territories (2.4 ± 0.9 vs. 1.6 ± 1.1; P = 0.002) and a higher overall perfusion score (20.1 ± 7.7 vs. 11.9 ± 9.4; P < 0.0001) per patient compared with standard-resolution. The number of segments with subendocardial ischaemia was greater with high-resolution acquisition (195 vs. 101; P < 0.0001). Hypoperfusion in all three territories was identified in 57% of 3VD patients by high-resolution compared with only 29% by standard-resolution ( P = 0.04). The area-under-the-curve (AUC) for detecting angiographic 3VD using the estimated MIB was significantly greater with high-resolution than standard-resolution acquisition (AUC = 0.90 vs. 0.69; P < 0.0001). Conclusion: In patients with angiographic 3VD, the ischaemic burden detected by perfusion CMR is greater with high-resolution acquisition due to better detection of subendocardial ischaemia. High-resolution perfusion CMR may therefore be preferred for risk stratification and management of this high-risk patient group.